The shipping industry as a source of fine black carbon particles in the marine environment: a preliminary study for the case study of Saronikos Gulf. - Mazioti, Aikaterini Anna; Kolovoyiannis, Vassilis; Zervakis, Vassilis; Krasakopoulou, Evangelia; Tragou, Elina; Hänninen, Risto; Sofiev, Mikhail; Majamaki, Elisa; Jalkanen, Jukka-Peka (Technical Annals, 2024)
Black carbon (BC) is a product of incomplete combustion. BC particles remain suspended in the atmosphere and BC is considered among the major “climate ac-tive pollutants”, influencing global climate change. In the current study, the at-mospheric deposition of fine BC particles (0.5 μm) and their fate in the marine environment of Saronikos Gulf (E. Mediterranean) was investigated, combining atmospheric modelling outcomes with marine modelling tools. The contribution of the shipping industry to the atmospheric deposition mass balances of BC was examined, for the year 2018. For the area of Saronikos Gulf, it was found that the yearly production of fine BC by shipping activities was approximately two orders of magnitude lower compared to the total deposition mass flux (g m2 y-1) of BC. The fate of this pollutant in the marine environment, due to transport processes, was examined by testing various configurations (i.e. particle settling velocities). The accumulation rate of fine particulate black carbon (PBC) finally settling onto the top sediment layer was quantified for each configuration.